Central Labour College, 1915 (page 1) (1915)
1915 1914-1918 "Central Labour College, 1915 (page 1)" [T0195.jpg], 1915 The Central Labour College (CLC) was founded in 1909 following the strike at Ruskin College, Oxford by student members of the Plebs League. The dissident students and the dismissed former Principal of Ruskin, Dennis Hird, moved the new college to London where it was financially supported by the South Wales Miners Federation and the National Union of Railwaymen. In 1915, after a persistent campaign by the CLC and its supporters, the TUC officially recognised the school and cooperated with it until its closure in 1929. The CLC expanded by organising more labour colleges that joined to form the National Council of Labour Colleges in 1921.